Effects of potassium dichromate on haematological. parameters in female and male Wistar albino RATS - Ounassa Adjroud (Ass. Univ. Bull. Environ. Res, 2009)
Hexavalent chromium is a potent toxic agent. It has been found to be carcinogenic in human and animal. The purpose of the current work is to compare the effect of potassium dichromate (K2Cr2O7) using variations in the dose, route of administration, and duration of exposure in male and female wistar albino rats with special focus on hematological parameters. K2Cr2O7 was administered either in the drinking water with a dose of 30 mg/l for 20 consecutive days to male wistar albino rats, or as a single dose subcutaneously (s.c) at 10, 50 and 100 mg/Kg body weight (b w) to female wistar albino rats. Control groups received NaCl 0.9% (0.3 ml s.c), or drinking distilled water. Haematological parameters were recorded on day 3, 6, and 21 after subcutaneous exposure, or on day 10 and 20 after oral treatment. 10 mg/Kg b w of K2Cr2O7 given subcutaneously induced during the first three days a marked decrease in the number of erythrocytes (-6%) of leucocytes (-30%) of platelets (-48%) and of hematocrit values (-15%), while the number of granulocytes is augmented (+124%) in comparison with control. Hemoglobin concentration and lymphocyte counts decreased markedly on day 6 after exposure. Chromium 50 mg/Kg b w, s.c mainly affected during the first three days the leucopoietic indices inducing leucopoenia (-55%), lymphopoenia (-57%), monocytosis (+104%), granulocytosis (+204%), and thrombocytosis (+38%) if compared with control, while the erythrocytic counts and hemoglobin concentration decreased from day 6 (-22%) and (-21%) respectively until day 21 (-41%) and (-36%) respectively, and hematocrit values decreased at the end of experiment (-36%) in comparison with control. The higher dose of chromium (100 mg/Kg b w, s.c) reduced during the first three days the number of erythrocytes (-20%), platelets (-20%), total leucocytes (-55%), lymphocytes (-59%) and augmented the number of monocytes (+56 %), and granulocytes (+166%), while on day 6 the number of platelets augmented (+27%) in comparison with control. In drinking water, 30 mg/l of chromium given to male wistar albino rats had no effect on all erythropoietic parameters studied with the exception of the elevation (+21%) in platelet counts at the end of exposure, while the number of lymphocytes and total leucocytes were significantly reduced on day 20 after exposure (-37%) and (-37%) respectively. Conversely, the number of granulocytes and monocytes markedly increased on day 10 after exposure (+42%) and (+22%) respectively if compared with control. Short-term exposures to low dose of K2Cr2O7, s.c induce in female wistar albino rats erythrocytopenia, thrombocytopenia, leucopoenia, lymphopaenia, granulocytosis, monocytosis, and a decrease in hematocrit values and hemoglobin concentration while in drinking water chromium was susceptible to affect in male rats the immune response inducing leucopoenia, lymphopoenia, monocytosis, and granulocytosis, while this oral route of exposure had no effect on erythropoietic parameters.